Analysis of Trust, Convenience, Financial Literacy, and Risk Perception on Shopee Pay Later Purchasing Decisions - Rizqullah, Naufal Arkan; Rahayu, Tri Septin Muji; Haryanto, Totok; Purnadi, Purnadi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this research was to analyze the effect of trust, convenience, financial literacy, and risk perception Shopee PayLater purchasing decisions in the Kemangkon District community. The study employed a purposive sampling technique to select 105 respondents who actively use Shopee PayLater. The Roscoe method was used to determine the sample size, while data analysis was conducted using multiple linear regression. The results revealed that trust, convenience, and financial literacy have a positive and significant influence on purchasing decisions. However, perceived risk does not significantly affect purchasing decisions. This research highlights the importance of fostering trust, improving user convenience, and enhancing financial literacy to encourage the adoption of financial technology services like Shopee PayLater.